Menstimulasi Perkembangan Matematika Anak Usia Dini melalui Pembelajaran Berbasis Bermain - Nopiana Nopiana; Misgiyati Misgiyati (Journal of Humanities, Social Sciences, and Education, 2025)
Early childhood mathematics development is a crucial foundation for children’s logical thinking, critical reasoning, and problem-solving abilities in later educational stages. Mathematics stimulation in early childhood is not intended to emphasize abstract concepts and formal arithmetic operations, but rather to introduce basic mathematical concepts through concrete experiences and meaningful play-based activities. This article aims to comprehensively examine the stimulation of early childhood mathematics development through play-based learning by reviewing mathematical development concepts, stimulation principles, learning strategies, and the roles of teachers and parents. A literature review method was employed by analyzing textbooks, national and international journal articles, and relevant educational policy documents. The findings indicate that systematic, contextual, and developmentally appropriate mathematics stimulation can effectively enhance children’s understanding of number concepts, patterns, geometry, measurement, and classification. Furthermore, a rich learning environment and positive interactions among children, teachers, and parents play a significant role in fostering positive attitudes toward mathematics from an early age. This article is expected to serve as a conceptual reference for early childhood educators in designing meaningful and developmentally appropriate mathematics learning experiences.